Evaluation of Effect of Various Nanofillers on Technological Properties of NBR/NR Blend Vulcanized Using BIAT-CBS System. (17th September 2013) - Thomas, Shaji P.; Thomas, Saliney; Marykutty, C. V.; Mathew, E. J.
Abstract : Owing to processing ease and resistance to oils and chemicals, NBR is widely used in many industries. But since neat NBR has only poor tensile properties, it is better to use suitable blends of NR and NBR after incorporating appropriate nanoingredients before vulcanization. It is well established that nanoparticles can be easily dispersed in a more uniform pattern in polymer matrix, thereby enhancing the technological properties of the elastomer vulcanizate. Since there are no systematic comparative studies on technological properties of NBR/NR blend containing different nanoingredients, efforts have been made in this study to investigate cure and technological properties like tensile properties, tear resistance, compression set, hardness, abrasion loss and swelling value of NBR/NR (80/20) blend vulcanizates containing stearic acid-coated nano-zinc oxide (ZOS), nano-BIAT, nano-silicate-coated CaCO3, PEO-coated calcium silicate, and surface-modified carbon nanotubes (CNT). XRD and electron microscopy have been used for morphological analysis. The nano ingredients were effective in enhancing the technological properties of the vulcanizates. Among the nanofillers, modified CNT was found to impart superior properties to NBR/NR blend due to more intercalation.